PENGARUH MANAJEMEN MODAL KERJA TERHADAP PROFITABILITAS (Studi pada Perusahaan Food and Beverages yang Terdaftar di BEI Tahun 2009-2013) - Firdausiah, Rr Ayu; Rahardjo, Toto (Jurnal Ilmiah Mahasiswa FEB, 2016)
The study aims to determine the effect of working capital management and profitability on food and beverage companies listed on the Stock Exchange Indonesian . This study describes the effect of the inventory period, receivable turnover period and the payable period  to the net profit margin of the company. This research is explanatory research by using census sampling technique. The  population of this study are 16 companies and the  sample consist of 13 companies within  2009-2013.  Working capital effect measurement used is multiple linear regression analysis. The research conducted  shows that inventory period, accounts receivable period, and the payable period are simultaneously influence to net profit margin. inventory period has negative affect to net profit margin partially while the receivables period had no effect on net profit margin.  This suggests that profitability will increase if the management company is able to plan the food and beverage inventory turnover period and the period of business with good debt. This suggests that profitability will increase if the management company is able to plan the food and beverage inventory turnover period and the payable period well. From those variable the one that influencing dominantly on the net profit margin food and beverage company is business payable period variable. Keywords: Working Capital Management, Profitability, Net Profit Margin